The UIG-1/CDC-42 guanine nucleotide exchange factor acts in parallel to CED-10/Rac1 during axon outgrowth in Caenorhabditis elegans. (2nd January 2021) - Cao, Wei; Deng, Shuer; Pocock, Roger
ABSTRACT: During development of the brain, neuronal circuits are formed through the projection of axons and dendrites in response to guidance signals. Rho GTPases (Rac1/RhoA/Cdc42) are major regulators of axo-dendritic outgrowth and guidance due to their role in controlling actin cytoskeletal dynamics, cell adhesion and motility. Functional redundancy of Rho GTPase-regulated pathways in neuronal development can mask the roles of specific GTPases. To examine potential Rho GTPase redundancy, we utilized a recently isolated hypomorphic mutation in a Caenorhabditis elegans Rac1 protein – CED-10(G30E) – which reduces the GTP binding and inhibits axon outgrowth of the PVQ interneurons. Here, we show that the CDC-42-specific guanine nucleotide exchange factor UIG-1 acts in parallel to CED-10/Rac1 to control PVQ axon outgrowth. UIG-1 performs this function in a cell-autonomous manner. Further, we found that transgenic expression of CDC-42 can compensate for aberrant CED-10(G30E)-regulated signalling during PVQ axon outgrowth. Together, our study reveals a previously unappreciated function for CDC-42 in PVQ axon outgrowth in C. elegans .